2020
DOI: 10.1073/pnas.2014520117
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric modulation of alternatively spliced Ca2+-activated Clchannels TMEM16A by PI(4,5)P2and CaMKII

Abstract: Transmembrane 16A (TMEM16A, anoctamin1), 1 of 10 TMEM16 family proteins, is a Cl−channel activated by intracellular Ca2+and membrane voltage. This channel is also regulated by the membrane phospholipid phosphatidylinositol 4,5-bisphosphate [PI(4,5)P2]. We find that two splice variants of TMEM16A show different sensitivity to endogenous PI(4,5)P2degradation, where TMEM16A(ac) displays higher channel activity and more current inhibition by PI(4,5)P2depletion than TMEM16A(a). These two channel isoforms differ in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 71 publications
0
24
0
Order By: Relevance
“…Membrane PI(4,5)P 2 would be more important for maintaining the channels in the fully open state with two Ca 2+ -binding sequences. Similarly, we report that the modulatory effects of PI(4,5)P 2 are stronger in unphosphorylated TMEM16A(ac) channels [ 10 ], suggesting that the binding of PI(4,5)P 2 to TMEM16A channels is dynamically regulated by allosteric changes in the channel structure.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Membrane PI(4,5)P 2 would be more important for maintaining the channels in the fully open state with two Ca 2+ -binding sequences. Similarly, we report that the modulatory effects of PI(4,5)P 2 are stronger in unphosphorylated TMEM16A(ac) channels [ 10 ], suggesting that the binding of PI(4,5)P 2 to TMEM16A channels is dynamically regulated by allosteric changes in the channel structure.…”
Section: Discussionmentioning
confidence: 80%
“…Our data showed how membrane PI(4,5)P 2 turnover modulates the TMEM16A channels in living cell membranes and revealed novel differences between the two isoforms of TMEM16A channels in the modulation by PI(4,5)P 2 . Our recent study revealed that the c-segment allosterically regulates the interaction of TMEM16A channels with PI(4,5)P 2 by altering the structure of PI(4,5)P 2 -binding sites on the channel protein, while it does not bind to PI(4,5)P 2 directly [ 10 ]. The activity of the TMEM16A(ac) channels is selectively decreased by the conversion of PI(4,5)P 2 to PI4P and remains inhibited until PI(4,5)P 2 is resynthesized.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ANO6-1-6 showed increased Ca 2+ sensitivity compared with that of ANO6, but it was not as high as that of ANO1, which is around 1 μM ( Pedemonte and Galietta, 2014 ; Tak et al, 2019 ; Yang et al, 2008 ). Other unknown mechanisms may be accountable for the remaining difference in Ca 2+ sensitivity, such as additional regulatory sites existing only in ANO1, different interactions with phospholipids, or unknown allosteric effects ( Feng et al, 2019 ; Ko et al, 2020 ; Xiao et al, 2011 ; Ye et al, 2018 ; Yu et al, 2019 ). Further studies are needed to fully understand the exact mechanisms.…”
Section: Discussionmentioning
confidence: 99%